Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan, Free Cash Flow, Leverage, dan Profitabilitas terhadap Manajemen Laba pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Yunita Sukma Ayu Wandirah; Etty Herijawati (eCo-Fin, 2025)
Companies frequently use earnings management as a tactic to sway financial reports, so that it can have an impact on decision making by stakeholders. This phenomenon is of particular concern in the rapidly growing infrastructure sector in Indonesia. This study's objective is to gather empirical data about the impact of managerial ownership, company size, free cash flow, leverage, and profitability on earnings management. The research sample is infrastructure companies that went public on the Indonesia Stock Exchange between 2020 and 2023. 56 firm-year observations in all and 14 selected businesses were obtained through the application of the purposive sampling method. Descriptive statistics, multiple linear regression analysis, traditional assumption tests, and hypothesis testing are all included in SPSS version 25, which was used to analyse the data. The outputs of the study show that management ownership has a 0.739 significant value, company size 0.079, free cash flow 0.020, leverage 0.116, and profitability 0.003. These findings indicate that managerial ownership, company size, and leverage do not have a significant effect on earnings management, while free cash flow and profitability have a significant effect on earnings management.